AI Integration and Teacher Performance in Peruvian Higher Education: An Empirical Study of Educational Dimensions - Riojas Rivera, Jimmy Ronald; Panta Chunga, Mary Inocencia; Romero Jáuregui, César Augusto; Del Castillo Castillo, Vladimir; Crespo Tintaya, Luz Marisol; Ampuero Joyo, Jenny Olga; Arapa Carrillo, Ruth Sara (LACCEI, 2025)
The integration of Artificial Intelligence (AI) in education is transforming teaching practices and influencing teacher performance. This study explores the correlation between AI adoption and key aspects of teacher performance, including personalized learning, classroom management, and assessment methodologies. Employing a quantitative research design, the study analysed survey responses from 65 university faculty members. Results indicate a moderate yet significant positive correlation between AI usage and teacher performance, particularly in areas such as space and time management, teaching resources, classroom climate, and evaluation methods. These findings underscore the potential of AI to enhance educational quality while highlighting the need for faculty training in AI tools to maximize their pedagogical impact. The study concludes that AI serves as a valuable pedagogical ally, enhancing teaching effectiveness and improving student engagement.